2009
DOI: 10.1042/bj20081422
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for the Glut1 PDZ-binding motif in growth factor regulation of Glut1 degradation and trafficking

Abstract: Cell surface localization of the glucose transporter, Glut1, is a cytokine-controlled process essential to support the metabolism and survival of hematopoietic cells. Molecular mechanisms that regulate Glut1 trafficking, however, are not certain. Here we show a C-terminal PDZ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 41 publications
2
65
0
Order By: Relevance
“…At steady state, GLUT1 is localized at the plasma membrane from where it undergoes continuous rounds of endocytosis and PDZ ligand-dependent endosome-to-plasma membrane recycling [9], the latter being mediated by the SNX27-retromer [8]. In the absence of retromer, GLUT1 accumulates in the lysosome and is degraded [8].…”
Section: Resultsmentioning
confidence: 99%
“…At steady state, GLUT1 is localized at the plasma membrane from where it undergoes continuous rounds of endocytosis and PDZ ligand-dependent endosome-to-plasma membrane recycling [9], the latter being mediated by the SNX27-retromer [8]. In the absence of retromer, GLUT1 accumulates in the lysosome and is degraded [8].…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that the 38-residue cytosolic tail of Glut1 is necessary for this localization pattern. The last four amino acids (DSQV) constitute a PDZ-binding motif that is necessary for an interaction with the protein GIPC (Bunn et al, 1999), which has been shown to regulate recycling of internalized Glut1 to the plasma membrane in hematopoietic cells (Wieman et al, 2009). Two other proteins, the small ubiquitin-like modifier (SUMO)-conjugating enzyme Ubc9 (Giorgino et al, 2000) and the lipid raft protein stomatin (Zhang et al, 2001;Zhang et al, 1999), have also been reported to associate with the cytosolic tail of Glut1.…”
Section: Fig 3 Immunogold Analysis Of Glut1 In Xenopus Retina Sectimentioning
confidence: 99%
“…Previous work in our laboratory has demonstrated that the membrane-rich outer segment is a preferred destination for membrane proteins heterologously expressed in tadpole rods and that exclusion of these proteins from the outer segment requires the presence of intrinsic targeting information to specify localization elsewhere in the cell (Baker et al, 2008). Because the cytosolic Cterminal tail of Glut1 has been implicated in the regulation of its intracellular trafficking in other cell types (Verhey et al, 1993;Wieman et al, 2009), we generated transgenic tadpoles expressing a truncated Glut1 construct (GFP-Glut138) lacking the entire C terminus. Strikingly, although this truncation did not prevent the protein from reaching the synaptic terminal and inner segment plasma membrane, it did allow the construct to gain entry into the rod outer segment, including the disc membranes (Fig.…”
Section: Active Exclusion Of Glut1 From Rod Outer Segments Of Transgementioning
confidence: 99%
“…Localization of GLUT1 to the cell surface is largely regulated through its endocytic traffic (5)(6)(7)(8)(9)(10)(11), controlled, in non-transformed cells, by cytokine stimulation (12,13) or energy stress (6). In cancer cells, several oncogenic lesions, including hyper activation of the EGFR/PI3K/AKT signaling pathway, induce accumulation of GLUT1 at the cell surface resulting in increased aerobic glycolysis (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%